True Resistant Hypertension Following Observed Drug Ingestion: A Systematic Evaluation. Issue 3 (20th August 2016) - Bunker, Jill; Chang, Choon‐Lan; Chapman, Neil; Poulter, Neil; Thom, Simon; Thornton‐Jones, Lucy; Sever, Peter
Abstract : The authors investigated the role of poor drug adherence in treatment‐resistant hypertension following observed drug ingestion in 102 patients. Median blood pressures (BPs) were 170/91 mm Hg at referral, 153/84 mm Hg prior to, and 142/79 mm Hg during a 4‐ to 6‐hour period after drug ingestion. Median daytime ambulatory BP monitoring (ABPM) over the following 24 hours was 142/80 mm Hg. Median BP at a final follow‐up clinic visit was 147/79 mm Hg. The cumulative number of patients achieving a goal of <140/90 mm Hg in clinic or <135/85 mm Hg mean on ABPM was 57 (56%), with a further nine (9%) controlled at the final follow‐up clinic visit. Thus, 65% of patients achieved a systolic BP <140 mm Hg at any point immediately prior to, or after, drug ingestion; the residual 35% were considered to have true resistant hypertension. In conclusion, among patients with suspected resistant hypertension, a minority were truly treatment‐resistant following observed drug ingestion and BP monitoring.